Increased pericardial fat accumulation is associated with increased intramyocardial lipid content and duration of highly active antiretroviral therapy exposure in patients infected with human immunodeficiency virus: a 3T cardiovascular magnetic resonance feasibility study. Issue 1 (December 2015) - Diaz-Zamudio, Mariana; Dey, Damini; LaBounty, Troy; Nelson, Michael; Fan, Zhaoyang; Szczepaniak, Lidia; Hsieh, Bill; Rajani, Ronak; Berman, Daniel; Li, Debiao; Dharmakumar, Rohan; Hardy, W.; et al.
Abstract Background The aim of the current study was to examine whether the use of highly active antiretroviral therapy (HAART) in patients with HIV is associated with changes in pericardial fat and myocardial lipid content measured by cardiovascular magnetic resonance (CMR). Methods In this prospective case-control study, we compared 27 HIV seropositive (+) male subjects receiving HAART to 22 control male subjects without HIV matched for age, ethnicity and body mass index. All participants underwent CMR imaging for determination of pericardial fat [as volume at the level of the origin of the left main coronary artery (LM) and at the right ventricular free wall] and magnetic resonance spectroscopy (MRS) for evaluation of intramyocardial lipid content (% of fat to water in a single voxel at the interventricular septum). All measurements were made by two experienced readers blinded to the clinical history of the study participants. Two-samplet -test, Spearman's correlation coefficient or Pearson's correlation coefficient and multivariable logistic regression were used for statistical analysis. Results Pericardial fat volume at the level of LM origin was higher in HIV (+) subjects (33.4 cm3 vs. 27.4 cm3, p  = 0.03). On multivariable analysis adjusted for age, Framingham risk score (FRS) and waist/hip ratio, pericardial fat remained significantly associated to HIV-status (OR 1.09, p  = 0.047). For both HIV (+) and HIV (-) subjects, pericardial fat volume showed strong correlation with intramyocardial lipid content (r  = 0.58, p < 0.0001) and FRS (r  = 0.53, p  = 0.0002). Among HIV (+) subjects, pericardial fat was significantly higher in patients with lipo-accumulation (37 cm3 vs. 27.1 cm3, p  = 0.03) and showed significant correlation with duration of both HIV infection (r  = 0.5, p  = 0.01) and HAART (r  = 0.46, p  = 0.02). Conclusions Pericardial fat content is increased in HIV (+) subjects on chronic HAART (>5 years), who demonstrate HAART-related lipo-accumulation and prolonged HIV duration of infection. Further investigation is warranted to determine whether increased pericardial fat is associated with higher cardiovascular risk leading to premature cardiovascular events in this patient population.